APLIKASI KELOLA ASET PADA DINAS PENDIDIKAN KABUPATEN PIDIE MENGUNAKAN TEKNIK LABELLING QR - CODE BERBASIS INTRANET - Rifky Harissandy; Sayed Achmady; Junaidi Salat (Sagita Academia Journal, 2024)
The Pidie Regency Education Service is one of the government agencies under the Pidie Regency Region which has the task of managing the education sector including data and information services, as well as education management services at kindergartens, elementary schools, middle schools, high schools and vocational schools in the Pidie Regency area. Asset management within the scope of the Pidie Regency Regional Education Service includes fixed assets and inventory assets. The naming system for inventory of goods within the Pidie Regency Education Office still uses handwriting. This method makes it difficult for property managers to identify inventory of goods because information regarding the inventory of goods cannot be written completely on the goods. For this reason, a naming system using a QR Code is needed that is capable of containing complete inventory information on goods. Goods managers only need to use an Android-based cellphone if possible to scan the QR Code on the goods inventory. By applying this QR Code labeling technique to the intranet-based Asset Management Information System at the Pidie Regency Education Office. Apart from making it easier to identify inventory items, it also makes it easier to create asset reports.